Functional supramolecular systems based on amphiphilic (thia)calix[4]arenes derivatives - Burilov, V. A.; Mailyan, M.; Solovieva, S. E.; Antipin, I. S. («Գիտություն» հրատ.)
Supramolecular chemistry is one of the most actively developing areas of modern science. The inexhaustible interest in supramolecular structures stems from their ability to self-assemble, that allows to create systems modeling processes occurring in living organisms, as well as to use nature's approaches to create such functional systems as molecular receptors, catalysts, nanoreactors, molecular machines, etc. For this reason, special attention of researchers working in the field of supramolecular chemistry is focused on amphiphilic molecules which are able to form highly ordered molecular ensembles in aqueous solutions. Amphiphilic macrocycles are of particular interest. A distinctive feature of amphiphilic macrocycles is their ability to high molecular recognition due to multipoint interactions. The modular approach of click chemistry (especially the copper-catalysed cycloaddition reaction of azides and alkynes, CuAAC), proposed by Sharpless in 2001 [1], is extremely suitable for the construction of amphiphilic structures based on macrocycles due to its exceptional tolerance to the introduced functional groups, allowing the direct introduction of even ionized fragments without the use of protecting groups. So, it is possible to synthesize libraries of various amphiphilic compounds by the changing of azide- or alkyne-containing structural modules [2,3] (Figure 3). Ակնարկային աշխատանքը ներկայացնում է համընդհանուր սինթետիկ մոտեցում մի շարք ամֆիֆիլային (թիա)կալիքս[4]արենների պատրաստմանը, ներառյալ երկֆունկցիոնալ ամֆիֆիլները՝ պոլիմերվող դիացետիլենային հատվածներով, CuAAC-պոլիմերացվող ամֆիֆիլներ, ինչպես նաև NHC–Pd(II) համալիրներ՝ օգտագործելով CuAAC/Մենշուտկինի ռեակցիան։ Հոդվածում բերվում են ստացված համակարգերի կիրառության մի քանի ուղղություններ և բնագավառներ: В настоящей работе представлен универсальный синтетический подход для получения ряда амфифильных (тиа)каликс[4]аренов, включающих бифункциональные амфифилы с полимеризуемыми диацетиленовыми фрагментами, CuAAC-полимеризуемые амфифилы, а также комплексы NHC – Pd(II) путем использование реакции CuAAC/Меншуткина. В обзоре продемонстрированы различные направления применения полученных систем.
Keywords: Organic chemistry